Policy process and food price crisis: A framework for analysis and lessons from country studies - Suresh Chandra Babu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
During the recent food crisis, developing countries responded with a wide variety of policy responses to protect their population. Understanding the policy-making process in developing countries is important to know why such policy responses are made and how various actors and players shape up and influence the policy decision-making. In this paper we develop a framework for analysing the policy process in developing countries and apply it to study the food policy process during the food price crisis in selected countries. A synthesis of policy process analysis in 14 developing countries indicate that policy responses may differ depending on the nature and magnitude of roles of various types of actors and players in the policy process. Political institutions and organizational infrastructure for policy consultations, strategic analysis, knowledge management and monitoring, and timely warning of food crisis and its impact can determine the policy process and its outcomes. Several lessons for improving the policy process are derived from the country studies.
Keywords: P48; Q18; R38; Z18; 330; policy process; food crisis; analytical framework; case studies; lessons